(untitled) (Emancipação, 2023)
In this article, we intend to discuss, using ecosocialist and degrowth theories and projects, two perspectives that seek to combine the radical critique of the capitalist system and its intrinsic logic of destruction of the environment, with a sustainable society project, based on another pattern of civilization. We chose to use centrally the productions of the two main authors of these two currents with an impact on Brazilian social thought: the Brazilian Marxist living in France Michael Löwy and the French Serge Latouche, respectively exponents of ecosocialism and degrowth. We seek critically debate the main arguments of criticism of the destructive logic of capital and the respective societal projects, as well as to point out the existing and possible articulations in both perspectives.